Response of Barley Variety Noor to Different Levels of DAP Fertilizer at Different Planting Dates - Hameed, Raad Ahmed; Ahmed, Husham Abdul-Rahman; Hayawi, Jasim Abdullah; Dhannoon, Alaa Younis (American Journal of Botany and Bioengineering, 2026)
Study was conducted at Rashidiya Research Station, Nineveh Governorate, during the 2024–2025 agricultural season to determine the optimal sowing date and DAP fertilizer level for the Noor barley cultivar. Three replications of a factorial experiment were set up in an RCBD design, including three sowing dates (15 Nov., 15 Dec., and 15 Jan.) and three DAP levels (0, 120, and 150 kg ha⁻¹). Results showed that sowing on 15 Nov. significantly outperformed other dates in plant height, biological yield, and grain yield, while 15 November and 15 Dec. were superior in spike number and grains per spike compared with 15 Jan. Fertilizer at 150 kg ha⁻¹ resulted in the tallest plants, whereas 120 kg ha⁻¹ achieved the best performance in most yield components. The interaction on 15 November with 150 kg ha⁻¹ yielded the highest values for growth and yield traits., highlighting the critical role of synchronizing sowing date and fertilization level to maximize barley productivity.